Fatal self-injury in the United States, 1999–2018: Unmasking a national mental health crisis. (February 2021) - Rockett, Ian R.H.; Caine, Eric D.; Banerjee, Aniruddha; Ali, Bina; Miller, Ted; Connery, Hilary S.; Lulla, Vijay O.; Nolte, Kurt B.; Larkin, G. Luke; Stack, Steven; Hendricks, Brian; McHugh, R. Kathryn; et al.
Abstract: Background: Suicides by any method, plus 'nonsuicide' fatalities from drug self-intoxication (estimated from selected forensically undetermined and 'accidental' deaths), together represent self-injury mortality (SIM)—fatalities due to mental disorders or distress. SIM is especially important to examine given frequent undercounting of suicides amongst drug overdose deaths. We report suicide and SIM trends in the United States of America (US) during 1999–2018, portray interstate rate trends, and examine spatiotemporal (spacetime) diffusion or spread of the drug self-intoxication component of SIM, with attention to potential for differential suicide misclassification. Methods: For this state-based, cross-sectional, panel time series, we used de-identified manner and underlying cause-of-death data for the 50 states and District of Columbia (DC) from CDC's Wide-ranging Online Data for Epidemiologic Research . Procedures comprised joinpoint regression to describe national trends; Spearman's rank-order correlation coefficient to assess interstate SIM and suicide rate congruence; and spacetime hierarchical modelling of the 'nonsuicide' SIM component. Findings: The national annual average percentage change over the observation period in the SIM rate was 4.3% (95% CI: 3.3%, 5.4%; p <0.001) versus 1.8% (95% CI: 1.6%, 2.0%; p <0.001) for the suicide rate. By 2017/2018, all states except Nebraska (19.9) posted a SIM rate of at least 21.0 deaths per 100, 000 population—the floor of the rate range for the top 5 ranking states in 1999/2000. The rank-order correlation coefficient for SIM and suicide rates was 0.82 ( p <0.001) in 1999/2000 versus 0.34 ( p = 0.02) by 2017/2018. Seven states in the West posted a ≥ 5.0% reduction in their standardised mortality ratios of 'nonsuicide' drug fatalities, relative to the national ratio, and 6 states from the other 3 major regions a >6.0% increase ( p <0.05). Interpretation: Depiction of rising SIM trends across states and major regions unmasks a burgeoning national mental health crisis. Geographic variation is plausibly a partial product of local heterogeneity in toxic drug availability and the quality of medicolegal death investigations. Like COVID-19, the nation will only be able to prevent SIM by responding with collective, comprehensive, systemic approaches. Injury surveillance and prevention, mental health, and societal well-being are poorly served by the continuing segregation of substance use disorders from other mental disorders in clinical medicine and public health practice. Funding: This study was partially funded by the National Centre for Injury Prevention and Control, US Centers for Disease Control and Prevention (R49CE002093) and the US National Institute on Drug Abuse (1UM1DA049412–01; 1R21DA046521-01A1).